Pengaruh Harga Dan Promosi Media Sosial Terhadap Keputusan Pembelian Msglow Di Arjowilangun Kalipare Malang Jawa Timur (Studi Pada Pengguna Ms Glow Di Arjowilangun Kalipare Malang Jawa Timur) - Devia Nicken Wulandari; N. Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine and analyze the effect of price and promotion on the purchasing decision of Ms Glow in Arjowilangun Kalipare, Malang, East Java, simultaneously or partially. The population in this study were all consumers of Ms Glow in Arjowilangun Kalipare, Malang, East Java. Samples were taken using the Slovin formula, in order to obtain 85 respondents who met the requirements as samples. The type of data used is primary data. Data was collected by distributing questionnaires to respondents. The technique used to analyze multiple linear regression. The results of this study indicate that (1) there is a simultaneous influence between price and promotion variables on purchasing decisions of Ms Glow consumers in Arjowilangun Kalipare Malang, East Java (2) Price variables affect purchasing decisions on consumers of Ms Glow in Arjowilangun Kalipare Malang, East Java ( 3) Promotional variables affect purchasing decisions on consumers of Ms Glow in Arjowilangun Kalipare, Malang, East Java. Keywords: Price, Promotion, Purchase Decision.